GEOSTAT1: A Prototype Expert System for the Explicit Knowledge Approach to Geostatistics - M. David (The Southern African Institute of Mining and Metallurgy, 1987)
This paper addresses the problem of technological transfer in geostatistics. Expert systems have become popular in certain fields because the needs of the industry are not provided for by traditional concepts and systems of education. The explicit knowledge approach in developing expert systems is presented through two experiments. The first describes a dedicated system written in GOLDEN LISP and the second a shell, using INSIGHT2, which has more general applications. Using expert systems forces on the user a new approach to parameter definition, and as an example an original method for the research of any anisotropy axes is developed which might well be useful in traditional programming. Two examples of application to a coal and a gold deposit are given.